Staying “One Step Ahead of a Racist”: Expanding Understandings of the Experiences of the Covid-19 Pandemic Among People From Minoritized Ethnic Groups Living in Britain - Karlsen, Saffron; Nelson, Rosie (Frontiers in Sociology, 2021)
Covid-19 has had a disproportionate impact on those in minoritized ethnic groups. Considerable attention has been given to evidence of ethnic inequalities in rates of infection, hospitalisation, and death. But other ways in which the pandemic experience has been affected by ethnicity have received less consideration. This paper explores the lived experiences of people in different minoritized ethnic groups living in South West England, during the UK’s first pandemic lockdown. Perceived positive opportunities for growth were offset by anxiety and stress, which were themselves compounded by an awareness of the additional risks they experienced as members of racialised groups, and a sense that this was being ignored – or intentionally exacerbated – by the British authorities. Frustration with an incompetent and corrupt national Government was intensified by concerns regarding their racist motives. Racism in wider society undermined confidence in key public institutions, such as the NHS and the police, while also producing barriers to informal local-community pandemic responses. Only through recognition of the particular ways in which the pandemic affected those in minoritized ethnic groups, including the multiple and compounding effects of current and historical racism, will it be possible to identify avenues for transformative systemic policy change and opportunities to rebuild trust and a better post-pandemic society for all.